Kidney transplantation from living donor with monolateral renal artery fibromuscular dysplasia using a cryopreserved iliac graft for arterial reconstruction: a case report and review of the literature - Rostand Emmanuel Nguefouet Momo; Paola Donato; Gabriele Ugolini; Francesco Nacchia; Luca Mezzetto; Gian Franco Veraldi; Stefano Marletta; Enrico Cavallo; Albino Eccher; Annamaria Giambanco; Daniela Cenzi; Luigino Boschiero (BMC Nephrology, 2020)
Abstract Background Aging and mortality of patients on waiting lists for kidney transplantation have increased, as a result of the shortage of organs available all over the world. Living donor grafts represent a significant source to maintain the donor pool, and resorting successfully to allografts with arterial disease has become a necessity. The incidence of renal artery fibromuscular dysplasia (FMD) in potential living renal donors is reported to be 2–6%, and up to 4% of them present concurrent extra-renal involvement. Case presentation We present a case of renal transplantation using a kidney from a living donor with monolateral FMD. Resection of the affected arterial segment and its subsequent replacement with a cryopreserved iliac artery graft from a deceased donor were performed. No intraoperative nor post-operative complications were reported. The allograft function promptly resumed, with satisfying creatinine clearance, and adequate patency of the vascular anastomoses was detected by Doppler ultrasounds. Conclusion Literature lacks clear guidelines on the eligibility of potential living renal donors with asymptomatic FMD. Preliminary assessment of the FMD living donor should always rule out any extra-renal involvement. Whenever possible, resection and reconstruction of the affected arterial segment should be taken into consideration as this condition may progress after implantation.